A Rationale for Using Sonoelastography in Thyroid Nodular Pathology - L. A. Timofeeva; L. B. Shubin (Вестник рентгенологии и радиологии, 2019)
Objective. To provide a rationale for using sonoelastography (SEG) in the differential diagnosis of thyroid cancer (TC).Material and methods. Thirty patients with thyroid nodules of various morphological structures were examined. The authors studied the data of SEG and immunohistochemistry (IHC) with monoclonal antibodies against types III and IV collagen (they evaluated the degree of the expressed collagen fibers). Analysis of variance, ROC analysis, and logistic regression were used (by comparing with the expression of collagens) to assess the predictive ability of ultrasound.Results. The study showed that irregular and uneven contours, microcalcifications, and “the height greater than the width” were most significant among the ultrasound signs in the diagnosis of TC. Cool colors prevailed when performing SEG in the pattern of thyroid cancer. Purple-blue hues were predominantly recorded (p<0.05 with regard to benign nodules), green ones were less frequently. ROC analysis of compression elastography showed that the area under the curve was 0.785 (95% CI 0.740-0.826), sensitivity 78.1%, specificity 79.0%. Comparison of the data of IHC and SEG revealed a direct correlation of tissue elasticity with the degree of a stromal component and with the presence of collagen-containing structures.Conclusion. SEG may suppose the probable nature of thyroid nodules on the basis of their morphological features. The low degree of the stromal component and the low content of types III and IV collagen make follicular colloid goiter and adenoma soft, which is recorded at SEG. TC is characterized by a high collagen level attributable to the characteristics of the metabolism of cancer cells, which makes them solid in the mode of SEG.